2013
DOI: 10.1007/978-94-007-6624-2
|View full text |Cite
|
Sign up to set email alerts
|

Self-Healing Phenomena in Cement-Based Materials

Abstract: Volume 11 RILEM, The International Union of Laboratories and Experts in Construction Materials, Systems and Structures, founded in 1947, is a non-governmental scientific association whose goal is to contribute to progress in the construction sciences, techniques and industries, essentially by means of the communication it fosters between research and practice. RILEM's focus is on construction materials and their use in building and civil engineering structures, covering all phases of the building process from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(17 citation statements)
references
References 4 publications
(4 reference statements)
0
15
0
2
Order By: Relevance
“…significant CaCO 3 precipitation was not observed in the first 14 days. Therefore, the healing in this period was attributed to other autogenous healing mechanisms, such as swelling of the crack walls and further hydration of non-hydrated dicalcium silicate (C 2 S) particles (de Rooij et al, 2013). The results of this study revealed that, in the first 2 weeks, the response of the biomortar to the presence of a crack is no different than a conventional mortar.…”
Section: Discussionmentioning
confidence: 79%
“…significant CaCO 3 precipitation was not observed in the first 14 days. Therefore, the healing in this period was attributed to other autogenous healing mechanisms, such as swelling of the crack walls and further hydration of non-hydrated dicalcium silicate (C 2 S) particles (de Rooij et al, 2013). The results of this study revealed that, in the first 2 weeks, the response of the biomortar to the presence of a crack is no different than a conventional mortar.…”
Section: Discussionmentioning
confidence: 79%
“…Self-healing phenomenon in concrete was identified early in the mid-nineteenth century by Lauer and Slate [2] and the concept was gradually established by several researchers [3][4][5][6][7]. The healing processes in concrete are classified broadly into two principal groups, autonomic and autogenous healing [8]. In the former, healing agents are encapsulated into the concrete or composites.…”
Section: Introductionmentioning
confidence: 99%
“…without human intervention. In the past 20 years, many different approaches for self-healing of concrete have been proposed [31,32]. Typically, two types of self-healing systems can be distinguished: capsule based systems, in which discrete capsules filled with self-healing agent are (randomly) dispersed in the cement matrix; and vascular systems, in which a connected network of channels is introduced in the cementitious matrix, with or without self-healing agent already stored in the network.…”
Section: Self-healing Concretementioning
confidence: 99%